Adaptation challenges in learning to teach EFL in a VUCA world: What have we learned from the COVID-19 experience? - Juan de Dios Martínez Agudo (DELTA: Documentação de Estudos em Lingüística Teórica e Aplicada, 2023)
ABSTRACT The COVID-19 pandemic has impacted education in general and teacher education in particular in various ways around the world. As teachers have played a leading role during the crisis, it is key that their voices be heard. Drawing on Vygotskian sociocultural theory as a framework for teacher professional development, this exploratory study seeks to make sense of the main adaptation challenges faced by 18 Spanish EFL teacher candidates in their learning-to-teach process in a practicum setting during the pandemic. Based on a narrative qualitative research design, a thematic content analysis was used for the qualitative data gathered through open-ended questions. Findings revealed that the crisis has resulted in teaching adaptation challenges in terms of traditional expository teaching models, difficulty in understanding and being understood as well as a lack of interaction and relationship with learners. Adaptability and reflective practice have proven to be key strategic features of professional competence in a volatile, uncertain, complex, ambiguous (VUCA) world.